Factors influencing the consumption of neglected and underutilized species by households in Atacora, Northern Benin - Bankole, Bissola (2023)
Presented at the International Scientific Days of Nutrition in Niger, February 2023 (Online). This presentation highlights the results of an evaluation on the consumption of Adansonia digitata, Ocimum gratissimum, Vigna radiata, and Moringa oleifera by households in Northern Benin